2021
DOI: 10.2169/internalmedicine.6326-20
|View full text |Cite
|
Sign up to set email alerts
|

Severe Coronavirus Disease 2019 That Recovered from Respiratory Failure by Treatment That Included High-dose Intravenous Immunoglobulin

Abstract: We herein report a case of severe coronavirus disease 2019 (COVID-19) in which high-dose intravenous immunoglobulin (IVIg) treatment achieved significant clinical improvement of deterioration of pulmonary inflammation after temporary clinical improvement. In the present case, clinical and radiological deterioration occurred despite a decrease in viral load, suggesting that deterioration was caused by reactivation of proinflammatory factors, such as tumor necrosis factor-α and interleukin-6, rather than direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 361 , 362 In a randomized, controlled trial including 84 COVID-19 patients, IVIg treatment did not demonstrate any therapeutic benefits in severe cases; however, a significant positive relationship between the number of days from admission to IVIg treatment and the length of hospitalization was observed, 363 which indicated the potential clinical benefit of IVIg administration during the early stage of COVID-19. In contrast, Suzuki et al 364 reported the potential efficacy of IVIg administration along with mechanical ventilation, methylprednisolone, favipiravir, ivermectin, and tocilizumab therapy in the late phase in an elderly patient with severe COVID-19.…”
Section: Interventions Targeting Multiple Cytokines and Pathwaysmentioning
confidence: 97%
“… 361 , 362 In a randomized, controlled trial including 84 COVID-19 patients, IVIg treatment did not demonstrate any therapeutic benefits in severe cases; however, a significant positive relationship between the number of days from admission to IVIg treatment and the length of hospitalization was observed, 363 which indicated the potential clinical benefit of IVIg administration during the early stage of COVID-19. In contrast, Suzuki et al 364 reported the potential efficacy of IVIg administration along with mechanical ventilation, methylprednisolone, favipiravir, ivermectin, and tocilizumab therapy in the late phase in an elderly patient with severe COVID-19.…”
Section: Interventions Targeting Multiple Cytokines and Pathwaysmentioning
confidence: 97%
“…Further, a significant correlation between IVIG treatment and increased survival rate and decreased COVID-19 progression has been shown ( 283 ). Moreover, the potential benefit of IVIG administration along with antiviral drugs and mechanical ventilation in severe COVID-19 patients has been reported ( 257 ). Conversely, IVIG administration, along with hydroxychloroquine and lopinavir/ritonavir, in the treatment of severe COVID-19 cases, has not been supported by recent findings ( 301 ).…”
Section: Therapeutic Approaches To Covid-19mentioning
confidence: 99%
“…1 study was found by manually searching ( Zeng et al, 2020 ).Of these, 1 meeting abstract, 2 not written in the English language, 40 not relevant, 2 reviews were excluded. The full text of 33 remained studies was assessed for eligibility and 12 case reports or case series ( Horii et al, 2020 ; Inoue et al, 2020 ; Ito et al, 2020 ; Nakamura et al, 2020 ; Scarpati, 2020 , Shibata et al, 2020 ; Shimazu et al, 2020 ; Zeng et al, 2020a ; Fukada et al, 2021 ; Sumimoto et al, 2021 ; Suzuki et al, 2021 ; Yamaya et al, 2021 ), 2 studies that did not report the results clearly ( Miyagami et al, 2021 ; Takeshita et al, 2021 ), 3 studies that did not classify patients based on disease severity ( Frix et al, 2020 ; Chen et al, 2021a ; Scotto et al, 2021 ) and 1 preprint study ( Alimova et al, 2020 ) were excluded. Finally, 15 studies identified as relevant and entered the quality assessment ( Awano et al, 2020 , d'Alessandro et al, 2020a , d'Alessandro and Cameli, 2020 , d'Alessandro et al, 2020b ; Frix et al, 2020 ; jp, 2020 , Saito et al, 2020 ; Wang et al, 2020 ; Xue et al, 2020 ; Anai et al, 2021 ; Bergantini et al, 2021 ; Chen et al, 2021 , d’Alessandro et al, 2021 ; Deng et al, 2021 ; He et al, 2021 ; Peng et al, 2021 ; Scotto et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%